Risk factors associated with multiple organ damage in childhood-onset systemic lupus erythematosus - Puengpipattrakul, Thanaporn; Lerkvaleekul, Butsabong; Pirojsakul, Kwanchai; Vilaiyuk, Soamarat (Frontiers in Pediatrics, 2023)
Objective: Previous studies have shown that approximately 39%-65% of patients with childhoodonset systemic lupus erythematosus (cSLE) have damage in at least one organ. Data on risk factors for organ damage in cSLE remain limited, especially in Asian populations. This study was conducted to evaluate the incidence of cSLE and identify the risk factors for accumulated organ damage in patients with cSLE.Methods: This was a retrospective study. Patients aged < 18 years who were diagnosed with cSLE between 2008 and 2020 were enrolled. Information on baseline characteristics, treatment, and disease activity assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) was collected from diagnosis until the most recent visits were reviewed from medical records. Disease damage was measured using the